2023
DOI: 10.3390/ijms24087422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol on Markers of Oxidative Stress and Sirtuin 1 in Elderly Adults with Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) affects a large part of the adult population and impairs its quality of life. Because of this, natural compounds with antioxidant, anti-inflammatory and hypoglycemic properties have been used as adjuvants. Among these compounds, resveratrol (RV) stands out, a polyphenol that has been studied in several clinical trials, the results of which are controversial. We conducted a randomized clinical trial on 97 older adults with T2D to evaluate the effect of RV on oxidative stress markers and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 75 publications
0
10
0
1
Order By: Relevance
“…The majority of them are randomized, double-blind and placebocontrolled trials. Among these trials, except one study that reported no measurable effects of resveratrol in T2DM patients 163 and another study that only reported changes in oxidative stress markers, 164 all other studies recorded positive results upon resveratrol administration, showing that resveratrol alone, or together with another anti-diabetic drug, can improve insulin resistance, increase antioxidant capacity, and reduce the levels of insulin, proinflammatory cytokines and blood glucose. [165][166][167][168][169] Variation in the modulation of biomarkers may be observed in different trials and to better compare the method, duration, dosage and outcome among trials, related information is listed in Table 5.…”
Section: Human Studies Of Resveratrol and Related Stilbenes In Managi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of them are randomized, double-blind and placebocontrolled trials. Among these trials, except one study that reported no measurable effects of resveratrol in T2DM patients 163 and another study that only reported changes in oxidative stress markers, 164 all other studies recorded positive results upon resveratrol administration, showing that resveratrol alone, or together with another anti-diabetic drug, can improve insulin resistance, increase antioxidant capacity, and reduce the levels of insulin, proinflammatory cytokines and blood glucose. [165][166][167][168][169] Variation in the modulation of biomarkers may be observed in different trials and to better compare the method, duration, dosage and outcome among trials, related information is listed in Table 5.…”
Section: Human Studies Of Resveratrol and Related Stilbenes In Managi...mentioning
confidence: 99%
“…165 Also, the upregulation of Nrf2 was noticed. 164 For other stilbenes, limited clinical trials were found, especially on hyperglycemia and diabetes. In a clinical study, patients with hypercholesterolemia were given 125 mg pterostilbene twice a day for 52 days and no adverse drug side effects on hepatic, renal and blood glucose markers were reported, proving that pterostilbene is safe for use at a dosage of 250 mg day −1 .…”
Section: Human Studies Of Resveratrol and Related Stilbenes In Managi...mentioning
confidence: 99%
“…In this context, García-Martínez et al demonstrated in a randomized clinical trial on adults with T2D that supplementation with resveratrol (with two doses: 1000 mg/day and 500 mg/day) resulted in an increase in the total antioxidant capacity, antioxidant gap, percentage of subjects without oxidant stress, and sirtuin 1 levels in comparison to those of the controls. Moreover, the observed antioxidant effect of resveratrol was more noticeable for the 1000 mg dose [ 131 ].…”
Section: Polyphenols Present In the Diet And Incidence Of Various Dis...mentioning
confidence: 99%
“…In a randomized controlled trial involving adults with type 2 diabetes, researchers noted that resveratrol exhibited antioxidant properties and influenced markers of oxidative stress by activating SIRT1. They observed a significant reduction in markers of oxidative stress, and a more efficient antioxidant effect was evident in patients who received a resveratrol supplement at a dose of 1000 mg/day compared to those receiving 500 mg/day, which was associated with increased levels of SIRT1 [ 38 ]. In a recent study discussing the oxidative stress effects of resveratrol, it was demonstrated that the depletion of SIRT1 abolished the beneficial effects of resveratrol and pterostilbene (PTS), a natural methylated analog of resveratrol.…”
Section: Sirt1 Activators and Atherosclerosismentioning
confidence: 99%